PENGARUH LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP KEMAMPUAN MANAJEMEN KEUANGAN UMKM DENGAN FINANCIAL TECHNOLOGY SEBAGAI VARIABEL MEDIASI - Nimas Aulia Pambajeng Miftahunnajah (Program Studi Magister Ilmu Manajemen Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
Objective This study aims to analyze the influence of financial literacy and financial inclusion on the financial management capabilities of MSMEs in Jepara Regency, with financial technology (fintech) as a mediating variable. This research is essential, considering that weak financial management remains a major barrier to the sustainability of MSMEs, despite increasing access to financial services through digital technology. Research Method. A quantitative approach was employed using a survey method involving 100 MSME actors from various business sectors in Jepara Regency. The sample was selected through purposive sampling. Data processing and analysis were carried out using the Structural Equation Modeling (SEM) technique with the Partial Least Squares (PLS) method, assisted by SmartPLS version 4.0. Results. The findings show that financial literacy has a positive and significant effect on financial management capabilities, while financial inclusion shows a positive but weak effect. Fintech serves as a moderating variable that strengthens the effect of financial literacy on financial management but weakens the effect of financial inclusion on financial management. Conclusion. This study concludes that the optimal use of fintech requires adequate financial literacy. Relying solely on expanding financial access without improving financial understanding may lead to ineffective financial management. Therefore, MSME empowerment strategies must emphasize the integration of financial literacy, financial inclusion, and the wise use of financial technology.